A familial Xp+ chromosome, dup (Xq26.3-->qter). Issue 11 (November 1995) - Vasquez, A I; Rivera, H; Bobadilla, L; Crolla, J A
Abstract : A maternally transmitted Xp+ chromosome was associated with an abnormal phenotype, including developmental delay and short stature, in two male cousins and their 12 year old aunt. The respective mothers were not mentally impaired but had short stature. The G banding pattern identified the extra chromosome segment as a repeat of Xq26.3-->qter attached to an apparently intact Xp22.3 sub-band, so the Xp+ chromosome may be described as rea(X)(Xqter-->p22.3::Xq26.3-->Xqter). The rearranged chromosome was late replicating in 97 to 100% of the metaphases in the mothers but it was early replicating in 43% of the lymphocytes in the mentally defective female (n = 100 cells/subject). Fluorescence in situ hybridisation using X and Y chromosome paints, as well as cosmids A and 1A1 specific for loci within Xq28, confirmed both the identity of the extra segment and the entirety of the Xp pseudoautosomal region. Therefore, the phenotypic consequences in this family can be related to the Xq26.3-->qter functional disomy allowing for the effects of X inactivation in the female carriers.